Real‐world evidence of brigatinib as second‐line treatment after crizotinib for ALK+ non‐small cell lung cancer using South Korean claims data (K‐AREAL) - Jeong Eun Lee; Jin Hyun Nam; Sun Hong Kwon; Bo Kyung Kim; Seung Min Ha (Cancer Medicine)
Abstract Purpose There is a lack of real‐world data in Asian populations for brigatinib, a next‐generation anaplastic lymphoma kinase (ALK) inhibitor for patients with non‐small cell lung cancer (NSCLC). This study analysed real‐world outcomes and dosing patterns for brigatinib in patients with crizotinib‐refractory ALK+ NSCLC in South Korea. Methods This retrospective, non‐interventional, cohort study used South Korean Health Insurance and Review Assessment claims data for adults with ALK+ NSCLC who initiated brigatinib between 19 April 2019 and 31 March 2021 after receiving prior crizotinib. Patients' characteristics, time to discontinuation (TTD), time to dose reduction, overall survival (OS) and treatment adherence were assessed. Results The study included 174 patients (56.9% male; 27.0% with a history of brain metastases). Median duration of prior crizotinib was 17 (range 0.3–48) months. Median follow‐up after brigatinib initiation was 18 (range 0–34) months. Overall, 88.5% of patients received full‐dose brigatinib (180 mg/day) and 93.1% of patients were adherent (proportion of days covered ≥0.8). The median TTD was 24.9 months (95% CI 15.2–not reached). The probability of continuing treatment was 63.2% at 1 year and 51.5% at 2 years. The probability of continuing at full or peak dose was 79.7% at 1 year and 75.6% at 2 years. Median OS was not reached. The 2‐year OS rate was 68.7%. Conclusions In this first nationwide retrospective study using national insurance claim data, brigatinib demonstrated real‐world clinical benefit as second‐line treatment after prior crizotinib in ALK+ NSCLC patients in South Korea.